GETTERING OF COPPER IN SILICON - PRECIPITATION AT EXTENDED SURFACE-DEFECTS - Decoteau, M; Wilshaw, P; Falster, R (Publ by Inst of Physics Publ Ltd, 1991)
Selected results from a TEM study of copper precipitation at extended surface defects in silicon are reported. The relative getting effectiveness of surface pits, oxidation induced stacking faults, and their bounding partials is compared. Copper-silicide precipitate colonies on {111} planes are observed for the first time and are found to nucleate at the bounding partials of oxidation induced stacking faults.